2018
DOI: 10.1038/s41419-018-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

PU.1/microRNA-142-3p targets ATG5/ATG16L1 to inactivate autophagy and sensitize hepatocellular carcinoma cells to sorafenib

Abstract: Sorafenib is currently the only systemic agent approved for treatment of advanced hepatocellular carcinoma (HCC). However, intrinsic and acquired resistance to sorafenib remains a great challenge with respect to improving the prognoses of patients with HCC. The cyto-protective functions of autophagy have been suggested as a potential mechanism by which chemoresistance or targeted drug resistance occurs in tumour cells. In the present study, miR-142-3p was identified as a novel autophagy-regulating microRNA (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…The expressions of hsa-miR-125a-5p, hsa-miR-107, hsa-miR-17-5p and hsa-miR-22-3p in HCC were consistent with published studies [30][31][32][33]. However, several studies have come up with results that were ambivalent with ours in hsa-miR-216b-5p, hsa-miR-142-3p and hsa-miR-20b-5p [34][35][36]. Since the heterogeneity of cross-studies cannot be ignored and the credibility of the combined results may decrease due to interfusion of the low-quality studies, more studies are needed to verify these results.…”
Section: Discussionsupporting
confidence: 90%
“…The expressions of hsa-miR-125a-5p, hsa-miR-107, hsa-miR-17-5p and hsa-miR-22-3p in HCC were consistent with published studies [30][31][32][33]. However, several studies have come up with results that were ambivalent with ours in hsa-miR-216b-5p, hsa-miR-142-3p and hsa-miR-20b-5p [34][35][36]. Since the heterogeneity of cross-studies cannot be ignored and the credibility of the combined results may decrease due to interfusion of the low-quality studies, more studies are needed to verify these results.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, a search for potential target genes of miR-874 in GC using several computational algorithms was performed. Among the potential targets, ATG16L1 was focused on as its function is associated with chemoresistance in cancer (29). The results of the present study revealed that the expression of ATG16L1 was increased in drug-resistant GC cells.…”
Section: Discussionmentioning
confidence: 64%
“…The ability of these miRNAs to restrain autophagy contributes to the sensitization of cancer cells to anti-cancer agents [95,97,100]. In addition to ATG5, the inhibitory effects of miR-142-3p on therapeutic resistance can be mediated by targeting ATG16L1 [97]. Moreover, a recent study also indicated that autophagy inhibition in miR-874-3p over-expressing cells abrogates therapeutic resistance [104] (Table 3).…”
Section: Mirnas Regulating the Lipidation Of Lc3mentioning
confidence: 99%
“…ATG5 can be targeted by multiple miRNAs, including miR-137-3p, miR-142-3p, and miR-224-3p. The ability of these miRNAs to restrain autophagy contributes to the sensitization of cancer cells to anti-cancer agents [95,97,100]. In addition to ATG5, the inhibitory effects of miR-142-3p on therapeutic resistance can be mediated by targeting ATG16L1 [97].…”
Section: Mirnas Regulating the Lipidation Of Lc3mentioning
confidence: 99%